Parathyroidectomy failures and causes evaluation (Journal of Academic Research, 2025)
Background: Persistent primary hyperparathyroidism (PHPT) after surgery is often due to missed ectopic or supernumerary glands. Reoperation is challenging and requires precise imaging, anatomical understanding, and surgical expertise.Methods: A 34-year-old woman with classic PHPT symptoms and biochemical evidence (Ca: 12.75 mg/dL, PTH: 891 pg/mL) underwent two failed parathyroidectomies. Imaging was inconclusive; histology showed nodular hyperplasia in the first and absence of parathyroid tissue in the second. A third surgery, guided by high-resolution ultrasound and intraoperative endoscopy, located an ectopic retroesophageal adenoma, which was excised.Results: Immediate postoperative laboratory confirmed cure (Ca: 7.2 mg/dL, PTH:
Keywords: Persistent hyperparathyroidism; reoperative parathyroid surgery; adenoma; Sestamibi scan; hormone (PTH)